HYDROBIOLOGICAL FEATURES OF THE KERALA BACKWATERS DURING PREMONSOON AND MONSOON MONTHS - DEVASSY, V P; GOPINATHAN, C K (Fishery Technology, 2025)
The hydro biological features like temperature, salinity,.phytoplankton, zooplankton and bottom fauna at twelve stations inthe Vembanad lake during pre-monsoon and monsoon monthswere studied and the results communicated in this paper.